The clinical significance of esophagogastric junction outflow obstruction and hypercontractile esophagus in high resolution esophageal manometry. Issue 10 (23rd May 2017) - Schupack, D.; Katzka, D. A.; Geno, D. M.; Ravi, K.
Abstract: Background: Although major manometric abnormalities, the significance of esophagogastric junction outflow obstruction (EGJOO) and hypercontractile esophagus (HE) is poorly understood. We sought to determine long term outcomes for EGJOO and HE. Methods: High‐resolution impedance manometry (HRIM) studies conducted from 5/30/2012 to 8/1/2014 consistent with EGJOO and HE and normal studies from 5/30/12 to 11/1/12 were identified. Standardized follow up was conducted with a phone survey utilizing the impact dysphagia questionnaire (IDQ‐10). Key Results: 56 EGJOO, 40 HE patients and 33 controls were identified. Structural evaluation with EGD and esophagram did not differ among groups. Use of opiates in EGJOO ( P <.05) and of anticholinergics in EGJOO and HE patients was more prevalent than in controls ( P <.005). Dysphagia was more common in EGJOO ( P <.05) and chest pain more common in HE ( P <.005) at presentation. While HE patients were more likely to be symptomatic ( P <.05), the majority of EGJOO and HE patients overall were asymptomatic at a mean 2.8 years follow up without medical or procedural intervention in the majority (72.5%). Symptom persistence at follow up was predicted by maximum distal contractile integral (DCI) and IRP in both EGJOO and HE ( P <.05). Conclusions & Inferences: The majority of patients with EGJOO and HE appear to have a benign clinical course similar to controls in the absence of specific treatment. However, the combination of abnormal IRP and DCI in both HE and EGJOO appears to discriminate an important subset of patients who may benefit from treatment. Further refinement of manometric criteria may therefore provide more useful clinical definitions of EGJOO and HE. Abstract : Although classified as major manometric abnormalities, the significance of esophagogastric junction outflow obstruction and hypercontractile esophagus is poorly understood. These abnormalities, when associated with other manometric and clinical findings may identify patients with associated symptoms, whereas these findings alone identify a substantial proportion of patients with likely incidental findings. Further refinement of the diagnostic criteria for these abnormalities may identify a subset of patients most likely to benefit from medical or surgical therapy.